Push pull microfluidics on a multi-level 3D CD - Thio, T.H.G.; Ibrahim, F.; Al-Faqheri, W.; Moebius, J.; Khalid, N.S.; Soin, N.; Kahar, M.K.B.A.; Madou, M. (2013)
A technique known as thermo-pneumatic (TP) pumping is used to pump fluids on a microfluidic compact disc (CD) back towards the CD center against the centrifugal force that pushes liquids from the center to the perimeter of the disc. Trapped air expands in a TP air chamber during heating, and this creates positive pressure on liquids located in chambers connected to that chamber. While the TP air chamber and connecting channels are easy to fabricate in a one-level CD manufacturing technique, this approach provides only one way pumping between two chambers, is real-estate hungry and leads to unnecessary heating of liquids in close proximity to the TP chamber. In this paper, we present a novel TP push and pull pumping method which allows for pumping of liquid in any direction between two connected liquid chambers. To ensure that implementation of TP push and pull pumping also addresses the issue of space and heating challenges, a multi-level 3D CD design is developed, and localized forced convection heating, rather than infra-red (IR) is applied. On a multi-level 3D CD, the TP features are placed on a top level separate from the rest of the microfluidic processes that are implemented on a lower separate level. This approach allows for heat shielding of the microfluidic process level, and efficient usage of space on the CD for centrifugal handling of liquids. The use of localized forced convection heating, rather than infra-red (IR) or laser heating in earlier implementations allows not only for TP pumping of liquids while the CD is spinning but also makes heat insulation for TP pumping and other fluidic functions easier. To aid in future implementations of TP push and pull pumping on a multi-level 3D CD, study on CD surface heating is also presented. In this contribution, we also demonstrate an advanced application of pull pumping through the implementation of valve-less switch pumping. Â© 2013 The Royal Society of Chemistry.